Analisis Studi Kelayakan Bisnis Dalam Aspek Produksi - Wahyuni Wahyuni; Muhammad Latiful Fatih; Raissa Muthia Syahrani Hsb; Sakina Sakina; Suhairi Suhairi (LPPM IAI Nasional Laa Roiba Bogor, 2022)
This article aims to determine the feasibility of a business in Production analysis. In this case the author uses a business feasibility analysis through the production aspect, which means the activities that arise when an idea in a planned business has shown opportunities and illustrates the advantages in terms of marketing. The problem of the production process and the operation process consists of the selection of production strategies, product selection and planning, quality planning, technology selection, production capacity planning, factory layout planning, layout planning, production quantity planning, inventory management and product quality control. Keywords: Business Feasibility Study, Production, Production Aspects,